Building a Bridge Among Unspoken Words: The Use of Drawing According to the IARA Model to Trigger Communication in Children and Adolescents Who Stutter - Cocco, Luisella; Anisio, Monica; Maulini, Claudia; Padovan, Anna Maria; Angilletta, Sonia; Kuvačić, Goran; De Giorgio, Andrea (Revista de Investigación en Logopedia, 2024)
Stuttering is a speech disorder characterized by frequent and significant problems with normal fluency and flow of speech. People who stutter perceive themselves as poor communicators and develop negative speech attitudes. This development of a negative communicative attitude could be related to the expectations and high demands made by their parents about fluency. When these expectations exceed the stuttering individual’s abilities to produce fluent verbal communication, a stuttering episode occurs. This is perceived by the individual as a communicative performance not adequately meeting the requests. Consequently, these individuals often resort to various avoidance and escape behaviors and generally avoid discussing their experiences and feelings related to stuttering. Therefore, stimulating communication is essential during speech therapy sessions to expose experiences otherwise kept hidden both from children/adolescents and their parents. However, encouraging communication is far from simple. In an attempt to facilitate communication and foster a more effective relationship between persons who stutter and their parents, we implemented the so-called awareness drawing according to the IARA model at the opening of the stuttering assessment session. Fourteen children (M=10; F=4; mean age=10.42; SD=1.65) and eight adolescents (M=6; F=2; mean age = 15.25; SD=1.03) diagnosed with stuttering were involved in this study, along with their relatives (28 parents; M=10; F=18; mean age=31.14; SD=4.66 years). The results of the study revealed that the drawings and comments of children and adolescents with stuttering, along with their parents, can offer valuable insights into their experiences and perceptions of stuttering. Children and adolescents expressed a desire for acceptance and a wish to be recognized beyond their stuttering. They depicted solutions that encompass the involvement of both parents and speech therapists. The utilization of awareness drawing can have a substantial impact on speech therapists. During the stuttering assessment session, it can provide valuable insights into the emotions, thoughts of person who stutter, as well as the experiences of their parents. This, in turn, can enhance the design of therapeutic intervention.
Keywords: stammering; stutter; speech therapist; emotion; awareness